Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.pedneo.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

First UTI episode in life in infants <1 year of age: Epidemiologic, clinical, microbiologic and disease recurrence characteristics

Abstract: Background: To examine the epidemiologic and microbiologic characteristics of first and recurrent UTI in young infants. Methods: A retrospective study of all infants <1 year hospitalized during 2014e2017 with their first UTI and followed during their first year of life. Results: 191 infants were enrolled; 69 (36.12%) patients were <2 months and 32 (16.8%) developed R-UTI during the follow-up. The five most common uropathogens were Escherichia coli, Klebsiella spp., Enterococcus spp., Proteus mirabilis and Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A total of 4 studies contained older children, and authors were unable to provide data specific to those <2 months of age. 7,10,31,32 Finally, 1 study was only published as an abstract without any outcome data. 33 Studies were published between 1978 and 2020 (Table 1) and reported on a median sample size of 143.5 (range: 12-3973) participants per study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of 4 studies contained older children, and authors were unable to provide data specific to those <2 months of age. 7,10,31,32 Finally, 1 study was only published as an abstract without any outcome data. 33 Studies were published between 1978 and 2020 (Table 1) and reported on a median sample size of 143.5 (range: 12-3973) participants per study.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%